2017
DOI: 10.18632/oncotarget.19349
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-regulated metabolic gene signature as a prognostic biomarker in non-small cell lung cancer

Abstract: Mutations in Kelch-like ECH-associated protein 1 (KEAP1) cause the aberrant activation of nuclear factor erythroid-derived 2-like 2 (NRF2), which leads to oncogenesis and drug resistance in lung cancer cells. Our study was designed to identify the genes involved in lung cancer progression targeted by NRF2. A series of microarray experiments in normal and cancer cells, as well as in animal models, have revealed regulatory genes downstream of NRF2 that are involved in wide variety of pathways. Specifically, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 81 publications
3
30
0
Order By: Relevance
“…Additionally, AKR1C2 may be considered as one of the biomarkers that indicates cisplatin resistance and may be act as one of the effective molecular targets for rescuing cisplatin sensitivity [42]. In agreement with our finding, Namani et al, have identified a gene expression signature that includes TXNRD1, AKR1C1, AKR1C2, and SRXN1 along with other genes in head and neck squamous cell cancer and non small cell lung cancer [43,44]. Interestingly, they found that higher expression of this gene signature is associated with poor survival and drug resistance.…”
Section: Agingsupporting
confidence: 90%
“…Additionally, AKR1C2 may be considered as one of the biomarkers that indicates cisplatin resistance and may be act as one of the effective molecular targets for rescuing cisplatin sensitivity [42]. In agreement with our finding, Namani et al, have identified a gene expression signature that includes TXNRD1, AKR1C1, AKR1C2, and SRXN1 along with other genes in head and neck squamous cell cancer and non small cell lung cancer [43,44]. Interestingly, they found that higher expression of this gene signature is associated with poor survival and drug resistance.…”
Section: Agingsupporting
confidence: 90%
“…In the background of TME, the disorder of tumor metabolism could deeply influence the multiple functions of malignant cancer cells [ 9 ]. Previous reports have identified metabolic signatures for prognostic prediction based on multiomics analyses in lung cancer [ 10 12 ]. However, the TME is a complex interaction network, and the integrated research on the roles of metabolic signatures in TME is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, examining the molecular mechanisms involved in these alterations by using publicly available data may contribute to the development and design of therapeutic targets for personalized/precision medicine in subsets of patients. Several emerging studies including our recent study on lung cancer have identified an NRF2-regulated gene signature and potential biomarkers for patient survival and NRF2 activity [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%